CITIZENSHIP BEHAVIOR AND SOCIAL EXCHANGE. - Konovsky, M. A.; Pugh, S. D. (Academy of Management Journal, 1994)
This article develops and empirically examines a social exchange model of organizational citizenship behavior. An employee's trust in a supervisor is proposed to mediate the relationship between procedural fairness in the supervisor's decision making and employee citizenship. Data from 475 hospital employees and their supervisors were consistent with our model. We discuss future research directions.